Analisis Pemahaman Konsep Bentuk Aljabar ditinjau dari Gaya Belajar Siswa - Titin Yuniarti; Supriyono; Puji Nugraheni; Wasiman (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
The aim of this study is to to describe students' understanding concepts in solving algebraic problems with visual, auditory, and kinesthetic learning styles. This research is a qualitative research with a qualitative descriptive method. The research subject was students of class VII SMP Negeri 2 Puring who had visual, auditory, and kinesthetic learning styles with 2 students' learning styles each. The technique of taking the subject uses purposive. The instruments used were questionnaires and tests. The results of this study show that (1) Understanding the concept of restating a concept on the elements of algebraic form fulfilled by students with visual and auditory styles. (2) classifying objects according to certain characteristics in determining similar and dissimilar terms and its reasons have not been fulfilled by all student learning styles. (3) providing examples and non-examples of the concept in determining similar and dissimilar tribes fulfilled by students with kinesthetic learning styles. (4) presenting concepts in various forms of mathematical representations in making mathematical models have not been fulfilled by all student learning styles. (5) use, utilize, and select certain procedures or operations in determining operations fulfilled by all student learning styles. (6) applying the concept or problem solving algorithm in applying the concept of algebraic forms has not been fulfilled by all student learning styles.